2021
DOI: 10.3390/rs13214403
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Permafrost Distribution in Western Himalaya Using Remote Sensing and Field Observations

Abstract: The presence and extent of permafrost in the Himalaya, which is a vital component of the cryosphere, remains severely under-researched with its future climatic-driven trajectory only partly understood and the future consequences on high-altitude ecosystem tentatively sketched out. Previous studies and available permafrost maps for the Himalaya relied primarily upon the modelled meteorological inputs to further model the likelihood of permafrost. Here, as a maiden attempt, we have quantified the distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 112 publications
2
21
0
Order By: Relevance
“…We compared our results with the previous research (Allen et al, 2016;Khan et al (2021) According to our results, in 2016, the probable permafrost covered 6.63% of Kullu district, while according to Allen et al (2016) and Khan et al (2021), the percentage area covered by permafrost is 9.56% and 47.92%, respectively (Figure 9a and Table 5). Similarly, in 2018, according to our map, 4.42% fell under permafrost, while Khan et al, (2021) mapped it to 47.34% area (Figure 9b). Our results are in better agreement with those of Allen et al (2016), but in contrast, Khan et al (2021) map overestimated the distribution of permafrost in the study area (Figure 9a).…”
Section: Comparison Of Results With Other Published Literaturementioning
confidence: 74%
See 2 more Smart Citations
“…We compared our results with the previous research (Allen et al, 2016;Khan et al (2021) According to our results, in 2016, the probable permafrost covered 6.63% of Kullu district, while according to Allen et al (2016) and Khan et al (2021), the percentage area covered by permafrost is 9.56% and 47.92%, respectively (Figure 9a and Table 5). Similarly, in 2018, according to our map, 4.42% fell under permafrost, while Khan et al, (2021) mapped it to 47.34% area (Figure 9b). Our results are in better agreement with those of Allen et al (2016), but in contrast, Khan et al (2021) map overestimated the distribution of permafrost in the study area (Figure 9a).…”
Section: Comparison Of Results With Other Published Literaturementioning
confidence: 74%
“…There are various methods of mapping the probable permafrost distribution of a region but the most widely applied method is by utilising MAAT (Baral et al, 2020;Hoelzle & Haeberli, 1995;Khan et al, 2021) and MAGT (Ran et al, 2018). Different researchers have used dataset from coarse resolution (WorldClim and MODIS) (Allen et al, 2016;Baral et al, 2020;Khan et al, 2021) to higher resolution (ASTER and Landsat) (Batbaatar et al, 2020;Pradhan & Shukla, 2022a). Khan et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biennial surface temperature of the rock glacier ranges from −5°C at upper altitude to more than 1.64°C in lower altitudes. The result of the recent permafrost model for western Himalaya (Khan et al, 2021) revealed that the rock glacier originates from a ‘discontinuous’ or ‘permafrost likely zone’ through ‘sporadic permafrost’ and flows down to a ‘no permafrost zone’. This reflects the fact that rock glaciers, with sufficient sediment input, can move far downslope such that their terminus position can be located at elevations where permafrost would otherwise not exist.…”
Section: Figurementioning
confidence: 99%
“…This warming has been attributed to a progressive increase in the atmospheric concentration of greenhouse gases (anthropogenic factors) since the mid of the 20 th Century (IPCC, 2014, Allen et al, 2019. The rapid climate change is expected to have a significant impact on the freshwater resources, biodiversity, ecosystems and human well-being in the Himalayas (Myers et al, 2000;Khan et al, 2021). The Himalayan region is crucial as it replenishes and maintains the water budget of the major rivers originating from the entire 'third pole area' and catering almost 20% of the world's population.…”
Section: Introductionmentioning
confidence: 99%